Optimalisasi Ceramah Spiritual (Islam) dalam Penurunan Tingkat Stres Penderita Kusta Reaktif - Haryanto, Joni; Lukitaningsih, (Jurnal Keperawatan Soedirman, 2009)
Leprosy disease still represents the problem of the world of very complex. The problem does not only from facet of health physic- but also extending until social problem, economic, cultural, security and national resilience. The big of stressor for leprosy will generate the disease transportation; journey going worse and optimalization deliver a lecture the spiritual (Islam) in degrading storey; level stress to leprosy reaction still need clarification. Research method is Quasy Experiment Design, sample taken by using techniques of purposive sampling with a number of 10 people at Hospital of Leprosy Sumber Glagah Mojokerto. Analyze by Wilcox on signed rank test, with the meaning storey; level 95%. Result of research show the decrease level of stress after conducted by discourse spiritual (Islam) at leprosy of type of Reversal and ENL that is by = 0,05, got by p = 0,003, From this research result is researcher suggest, for it self leprosy to develop; build the adaptive coping which do not get out of the support of family of society fund, and also for health worker that is Nurse can identify and implementation with a way of develop; building adaptive coping and can decreasing the level of stress leprosy.